2019
DOI: 10.3389/fonc.2019.01311
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Eukaryotic Translation Initiation Factor 4A Against Breast Cancer Stemness

Abstract: Breast cancer stem cells (BCSCs) are intrinsically chemoresistant and capable of self-renewal. Following chemotherapy, patients can develop minimal residual disease due to BCSCs which can repopulate into a relapsed tumor. Therefore, it is imperative to co-target BCSCs along with the bulk tumor cells to achieve therapeutic success and prevent recurrence. So, it is vital to identify actionable molecular targets against both BCSCs and bulk tumor cells. Previous findings from our lab and others have demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…Importantly, eIF4A1 and eIF4E were found to be independent predictors of poor outcome in ER-negative breast cancer [13]. Recently, we indicated a role for eIF4A1 in facilitating paclitaxel resistance in TNBC cell lines [14].…”
Section: Introductionmentioning
confidence: 91%
“…Importantly, eIF4A1 and eIF4E were found to be independent predictors of poor outcome in ER-negative breast cancer [13]. Recently, we indicated a role for eIF4A1 in facilitating paclitaxel resistance in TNBC cell lines [14].…”
Section: Introductionmentioning
confidence: 91%
“…While the loss of ALDHs coincides with complete loss of glucose utilization in both KO clones, the causal effect, if any, between these two events will need further investigation. Future studies will be needed to confirm if LDHA/B inhibitors could be combined with ALDH inhibitors to evoke a more significant chemotherapeutic effect of drugs and radiation (48), and could be explored with ALDH inhibitors such as (-)epigallocatechin gallate (65,66), rocaglamide A (67), NCT-501 (67), and ellagic acid (68).…”
Section: Reduction In Aldehyde Dehydrogenase Transcripts (Aldhs)mentioning
confidence: 99%
“…In 2007, Li et al 37 firstly identified pancreatic CSCs using CD44 (+)CD24(+)ESA(+) as surface markers. Since then, pancreatic CSCs have been recognized in succession by using various surface markers, including CD133, 29 CD44, 38 CD24, c‐met and ALDH 39 . In the present study, we identified pancreatic CSCs using CD133 as a surface marker and found that the proportion of CSCs in PC cells was significantly elevated as to normal HPDE cells.…”
Section: Discussionmentioning
confidence: 51%